Intrahepatic Cholestasis in Non-Alcoholic Fatty Liver Disease: Pathogenesis and Role of Ademetionine in Treatment - Ye. N. Shirokova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to evaluate features of intrahepatic cholestasis (IHC) pathogenesis in non-alcoholic fatty liver disease (NAFLD), as well as role of ademetionine in treatment of this condition.Key statements. NAFLD is the most frequent chronic diffuse liver disease. Increase in proportion of people with excess weight, obesity, and metabolic dysregulation leads to higher rates of NAFLD. Concomitant IHC is present in 30 % of NAFLD patients, while it is associated with more active disease course and possible worsening of prognosis. Impairment of adipocyte and hepatocyte metabolism, gut dysbiosis, and inherent factors are recognized as significant factors for NAFLD development. In NAFLD patients most of IHC cases are related to functional cholestasis. IHC in NAFLD is associated with increased risks of fibrosis and all-cause death. Ademetionine may restore transmethylation and improve rheologic properties of hepatocyte membranes in liver disease. In IHC patients treatment with ademetionine led to decreased serum bilirubin concentrations, as well as lowering of the liver transaminases' and alkaline phosphatase activities. At the same time improvement of symptoms severity, including itching, was noted. Taking into account the efficacy of ademetionine in IHC in NAFLD patients, its' use was included in the national clinical guidelines.Conclusion. Use of ademetionine in NAFLD with concomitant IHC is feasible from pathogenesis perspective and may be effective in clinical practice.